The Mason papers : selected articles and speeches - Mason, Anthony, Sir, 1925-; Lindell, Geoffrey (Annandale, NSW : Federation Press, 2007)
Sir Anthony Mason has been a prominent public figure for over 40 years in Australia. He was Commonwealth Solicitor-General, a Member of the NSW Court of Appeal, a Justice and Chief Justice of the High Court of Australia. The Mason Papers discusses the role of the judge and judicial independence in a modern Western democracy
Includes bibliographical references and index
Keywords: Law -- Australia; Judges -- Australia